2017
DOI: 10.3390/ijms18122715
|View full text |Cite
|
Sign up to set email alerts
|

Femtograms of Interferon-γ Suffice to Modulate the Behavior of Jurkat Cells: A New Light in Immunomodulation

Abstract: Since interferon-γ (IFN-γ) tunes both innate and adaptive immune systems, it was expected to enter clinical practice as an immunomodulatory drug. However, the use of IFN-γ has been limited by its dose-dependent side effects. Low-dose medicine, which is emerging as a novel strategy to treat diseases, might circumvent this restriction. Several clinical studies have proved the efficacy of therapies with a low dose of cytokines subjected to kinetic activation, while no in vitro data are available. To fill this gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In this paper, the developed method was used for the study of water protein solutions (interferon-gamma (IFNγ), antibodies to interferon-gamma (Ab to IFNγ)) and glycine buffer (GB) at low concentration. The issue of sensitivity when dealing with low concentrations is of utmost importance, in particular, given the fact that some studies [2][3][4][5][6][7] have revealed the effects observed in protein solutions at low concentrations that can hardly be explained directly by the properties of protein and the solvent, i.e., water. Furthermore, the present study analyzed the properties of the protein (IFNγ) dissolved in the above-mentioned solutions at low concentration.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the developed method was used for the study of water protein solutions (interferon-gamma (IFNγ), antibodies to interferon-gamma (Ab to IFNγ)) and glycine buffer (GB) at low concentration. The issue of sensitivity when dealing with low concentrations is of utmost importance, in particular, given the fact that some studies [2][3][4][5][6][7] have revealed the effects observed in protein solutions at low concentrations that can hardly be explained directly by the properties of protein and the solvent, i.e., water. Furthermore, the present study analyzed the properties of the protein (IFNγ) dissolved in the above-mentioned solutions at low concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning IFN-γ, low-doses of SKA IFN-γ potentiated the activity of natural killer cells isolated from patients with early-stage colon cancer 28 . In Jurkat cells, low-dose SKA IFN-γ exerted an immunomodulatory action by tuning signal transduction and gene expression 18 .…”
Section: Discussionmentioning
confidence: 99%
“…10 ng/ml of vascular endothelial growth factor (VEGF) (PeproTech London UK) were used as positive control. The cells were stained with crystal violet to visualize the width of the wound and images were captured with a 4X objective using a phase contrast microscope 18 . The wound area was calculated by ImageJ software and expressed using an arbitrary value scale.…”
Section: Migration Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Of fundamental importance in understanding the mechanisms of regulation of inflammatory response was the model of the immune balance, that is, the reciprocal relationships between some lymphocyte subpopulations, T-helper 1 (Th1), Th2, regulatory T cells (T-reg) and Th17. Preclinical and clinical studies on the use of multicomponent/multitarget drugs [ 32 , 33 , 34 , 35 , 36 , 37 ] and physiological low dose cytokines [ 38 , 39 , 40 , 41 , 42 , 43 ] have opened new scenarios on the possibilities of treating acute and chronic inflammatory diseases (also on an autoimmune basis).…”
Section: Low Dose Drugs For the Management Of Acute And Chronic Inflammationmentioning
confidence: 99%